ESL tertiary studens' writing needs: a framework for a supplementary online writing program - Noriah Ismail,; Saadiyah Darus,; Supyan Hussin, (Penerbit Universiti Kebangsaan Malaysia, 2012)
This article discusses the elements essential for developing a supplementary online writing program for tertiary students of English as a Second Language (ESL) at University Teknologi MARA, Johor Branch, on the basis of a framework derived from the results of a needs-analysis study. The participants in this study were sixty Part Three Diploma students taking the BEL 311 compulsory general English proficiency course, and four writing lecturers, each of whom had taught the course for more than five years. The students filled out a needs-analysis questionnaire; the lecturers were interviewed. The findings revealed not only learning and writing problems among students but also, most importantly, the elements that are perceived by students and lectures as essential for developing a supplementary online writing program. These elements include aspects pertaining to critical thinking, autonomous learning, social interaction, and learner interest.